(untitled) (Revista Espinhaço, 2025)
This study aimed to assess the geodiversity of the municipality of Maragogipe, Bahia, through the application of the Geodiversity Index (GI), with the objective of identifying priority areas for geoconservation and geotourism potential. The methodology comprised an integrated analysis of geological, geomorphological, pedological, structural, and hydrographic data, processed using geotechnological tools. Spatial mapping of the GI revealed a heterogeneous distribution of physical environment elements, with emphasis on the central and east-central regions of the municipality, where natural attribute diversity is maximised. These areas present favourable conditions for the establishment of geotourism activities, linking the local geological and geomorphological heritage with the region’s rich historical and cultural context. The findings contribute to sustainable environmental and tourism planning and provide a basis for future geoconservation and geoeducation measures. The study underscores the relevance of applying the Geodiversity Index as a diagnostic and territorial management instrument aimed at enhancing local geopatrimony, further noting that although the municipality exhibits considerable tourism potential intertwined with its history and culture, it currently lacks an adequate administrative framework to support tourism development.